Teaching effectiveness: Basis for the development of assessment tool - Aquino, John Michael Del Rosario; Chavez, Maria Asela (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2022)
Teachers have an important role to play in delivering quality education (SDG4). The quality of teaching that they deliver to students greatly affects them. This participatory action research (PAR) argues that there are gaps that need to be addressed in teaching effectiveness; (a) developing conceptual framework anchoring in common theory that served as a lens of the study, (b) measure it to ensure that students receive quality education and acquire the skills they need for national development, and (c) develop an assessment tool. This research designed a conceptual framework on teaching effectiveness based on the results of the focus group discussions with key informants (bottom-up evaluation) in selected mid-level administrators (coordinators), teachers, students, and alumni from selected sectarian higher education institutions. The researchers also developed indicators and identified items to assess teacher effectiveness through an assessment tool. Teaching effectiveness argues that key players i.e., Teacher’s Pedagogy, Content, and Knowledge, Learner’s performance in school, and adaptation of institutions in Outcomes-Based education are important components in a learning organization. The results revealed that the teaching effectiveness is evident in teachers who exhibit pedagogy, content and knowledge, possess good qualities, humanistic and professional approach, adopt and use varied technologies and online applications to facilitate learning, employ life integration in their lessons, anchored on the school’s VMGO, program, course outcomes, and activities. It contributes to student learning. This research concludes that the indicators revealed on the PAR must be used for further research specifically in designing an assessment tool in measuring teaching effectiveness.